Online training for substance misuse workers: A systematic review. (2nd November 2017) - Calder, Robert; Ainscough, Tom; Kimergård, Andreas; Witton, John; Dyer, Kyle R.
Abstract: Effective dissemination from researchers to clinicians can improve outcomes for people using substance misuse services by providing the knowledge and skills necessary to deliver best practice. The internet has the potential to facilitate quick, accurate and affordable learning on a large scale. However, the quality of online resources for substance misuse worker training is rarely evaluated. Aim : To review the available literature on the learning outcomes, qualitative descriptions and costs of online learning. Methods : The literature on online learning, staff training and substance misuse were reviewed following PRISMA guidelines. Findings : Sixteen articles were identified with large variation in study quality and design. Descriptions of online interventions were insufficient for replication or comparison. Good quality online training should meet the needs of substance misuse workers whilst acknowledging that these needs will differ according to worker and context. Conclusions : Published research into online learning for the substance misuse workforce should be sufficient in detail to enable replication and direct comparison. More qualitative research about the needs and preferences of the workforce using online learning would fill a notable gap in the literature.